1977
DOI: 10.1007/bf00410776
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of 14C-labelled lignin and phenols by a Nocardia sp.

Abstract: A Gram-positive bacterium which was isolated from a Finnish soil and identified as a Nocardia sp., was able to decompose lignin and to assimilate lignin degradation products as a carbon source. It could release 14CO2 from 14C-labelled methoxyl groups, side chains or ring carbons of coniferyl alcohol dehydropolymers (DHP) and from specifically 14C-labelled lignin of plant material. Furthermore, it could release 14CO2 from phenolcarboxylic and cinnamic acids and alcohols labelled in the OCH3, COOH groups, side c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 13 publications
1
36
0
2
Order By: Relevance
“…The bacterium was originally isolated from a Finnish soil for its ability to decompose lignin and use lignin degradation compounds as a carbon source (Trojanowski et al 1977).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterium was originally isolated from a Finnish soil for its ability to decompose lignin and use lignin degradation compounds as a carbon source (Trojanowski et al 1977).…”
Section: Methodsmentioning
confidence: 99%
“…A minority of sequences were similar to members of Rhodococcus, Nocardia and Mycobacterium, which are commonly found in soil and water and include human pathogens, saprophytes (Ryan, 2004) and decomposers able to process complex aromatics (van der Geize and Dijkhuizen, 2004), lignin (Trojanowski et al, 1977;Haider et al, 1978) and complex hydrocarbons such as petroleum distillates (Aislabie et al, 1998).…”
Section: Fungal and Actinobacterial Sequencesmentioning
confidence: 99%
“…But the present study confirms that when the coir pith was treated with the mushroom Pleurotus sajor caju, the nutrient content of coir pith such as Nitrogen, Phosphorous and Potassium showed the variation and it get increased. In addition to the fungi, several reports brought strong evidence of some bacteria can degrade lignin effectively (Crawford, 1978;Haider et al, 1978;Kawakami., 1976;Trojanowski et al, 1977). Cullen and Kersten (2004) reported that the enzymes from white rot fungi that catalyse the initial depolymerization of lignin are extra cellular and unusually non specific.…”
Section: Resultsmentioning
confidence: 99%